Pengaruh Insentif Finansial terhadap Kinerja Karyawan UMKM Mie Gacoan di Ungaran - Dakhi, Berlian; Yuliamir, Henry (Mahesa Research Center, 2025)
This study aims to analyze the influence of financial incentive strategies on improving human resource (HR) performance at the Mie Gacoan Ungaran MSME. The main issues addressed are fluctuations in work motivation and instability in employee productivity. The research method used was a qualitative case study approach. Data were collected through in-depth interviews and participant observation with eight informants: the owner, operational manager, supervisor, and employees. The data analysis technique used the Miles and Huberman interactive model. The results indicate that daily and weekly bonuses, attendance allowances, overtime pay, and customer review-based incentives have a positive effect on improving employee morale and service quality in the short term. However, extrinsic incentives are not able to foster sustainable internal motivation. This research's conceptual contribution enhances understanding of the limitations of financial incentive strategies when not accompanied by non-financial approaches such as work recognition and career development. This study recommends the development of an integrated reward system that balances financial and non-financial aspects to improve HR performance at MSMEs.